On a Leasing Variant of the Online Connected Facility Location Problem - de Lima, Murilo Santos; San Felice, Mário César; Lee, Orlando (Anais do Encontro de Teoria da Computação (ETC); 2016: Anais do I Encontro de Teoria da Computação, 2016)
In the leasing optimization model, resources are leased for K different time periods, instead of being acquired for unlimited duration. The goal is to use these temporary resources to maintain a dynamic infrastructure that serves n requests while minimizing the total cost. We propose and study a leasing variant of the online connected facility location problem, which we call the online connected facility leasing problem. In this problem each client that arrives must be connected to a temporary facility, which in turn must be connected to a root facility using permanent edges. We present an algorithm that is O(K · lg n)-competitive if the scaling factor is M = 1.